Adabul Alim Wal Muta’allim: Study Of Classic Book In Answering Educational Challenges - Maisaroh, Mela Siti; Kurniasih, Dwi; Khoiriyah, Maulida Amanatul (SHAHIH: Journal of Islamicate Multidisciplinary, 2021)
ThisstudyaimstoexplainthestudyofthebookAdabulAlimwalMuta’allim in answering the challenges of education. The book is a classic book that is usually studied in Nusantara pesantren and written by KH Hasyim Asy'ari for knowledge seekers and teachers. The method used in this study is qualitative descriptive. Qualitative descriptive method is a method that attempts to describeobjectsclearlyandclearly.Thedatasourceinthisstudyisintheform oflibrarydatasources,namelytheAdabulAlimwalMuta'allimbookreviewed basedoncontentanalysis.TheresultsofthisstudyindicatethatinAdabulAlim wal Muta'allim examines the concept of Islamic pedagogic science which contains ethics, manners, and morals in seeking knowledge. Besides that, Islamic pedagogic concepts in the book are very relevant and able to answer the challenges of education today.